Peningkatan Maharah Kitabah dengan Menggunakan Metode Imla pada Anak Usia Dini Kelas B TK Plus Annaba Pasawahan Purwakarta - Syifa Nur Fauziyah; Dede Rizal Munir (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to improve the Arabic writing skills (maharah kitabah) of young children in Class B at TK Plus Annaba Pasawahan Purwakarta for the 2023/2024 academic year using the imla method. The imla method, which involves dictation techniques, is considered effective in helping children develop listening skills, concentration, fine motor skills, and memory abilities. This type of research is Classroom Action Research (CAR), where the teacher also acts as the researcher and implements the teaching. The research design follows the Kemmis and McTaggart model. This study was conducted in the second semester of the 2023/2024 academic year, specifically in April. The subjects of this study were 28 students in Class B at TK Plus Annaba Pasawahan. The object of this study is the Arabic writing skills of young children. Data collection was carried out through tests, observations, and research. The results showed that the imla method significantly improved the students' ability to write Arabic letters correctly. The students experienced an increase in Arabic writing skills with the imla method, from 62,14% in Cycle I to 75,00 % in Cycle II.